Character Education in Social Science Lessons at State Vocational High School 1 Seputih Agung Lampung Tengah - Cheri Saputra (International Journal of Educational and Life Sciences, 2024)
Education is a conscious and planned effort carried out together in order to make students fully human beings with the development of their potential and become human beings with the one and only god. And by having cognitive, affective and personal intelligence and skills needed in the future both for himself, the nation and the community. To realize the goals of national education, it is necessary to inject and intervene in the implementation of education, which in this case is a curriculum that can be a reference in the process of implementing education. Related to the above, this study aims to determine whether the learning process that has been carried out by social studies teachers has applied character education values to students at SMKN 1 Seputih Agung. The method used in this study is a qualitative descriptive method, using this method is expected to be able to explain and answer the formulation of existing problems so as to get the data needed in this study. Data analysis techniques use interactive analysis consisting of three flows, namely data reduction, data presentation and conclusions. About the results of this study, it can be concluded that: (1) Efforts to shape character at SMK Negeri 1 Seputih Agung involve several aspects, such as (a) morning interaction and religious activities, (b) participation in extracurricular activities, (c) integration of character in learning activities, and (d) various teaching methods used by teachers, such as lectures, dialogues, discussions, roles, and presentations. (2) The integration of character education in social studies subjects is documented in the Learning Implementation Plan. (3) The character building process is strengthened by factors such as qualified human resources and adequate school facilities. (4) On the other hand, there are several inhibiting factors, such as lack of moral understanding of students and lack of attention from parents.